The Characteristics, Socialization by Parents and the Perception of Youth towards Employment in Agriculture in Indonesia - Gandasari, Dyah; Sulistyowati, Dwiwanti; Kusmiyati; Juhdi Muslihat, Elih (International Journal of Psychosocial Rehabilitation, 2020)
Census 2003 and 2013 results showed that the number of agricultural business households in Indonesia decreased by 16.32 percent. There was a shift in labor from agriculture to non-agriculture. It was suspected that there was a lack of interest in youth in agriculture. Consequently, the young generation would not necessarily inherit the agricultural skills of their parents or community. Therefore, the characteristics, socialization by parents and the perception of youth towards employment in agriculture become interesting topics to be studied. The study was conducted in one school in the agricultural center area in Lembang District, West Bandung, West Java. The method used in this study was a survey, and the target sample was 88 unmarried youth from 13 to 24 years old. The result of the study showed that: 1) Respondent Characteristics (a) Gender: 51% male; and 49% female; (b) Age category: adolescents (mid-15-17) 91%; and late adolescents 9%, and (c) The majority of respondents (40%) have a high level of cosmopolitanism by visiting other villages or cities more than 3 times in the past month; 32% of youth have a low cosmopolitan level (0-1 times in one month) and 28% of youth have moderate cosmopolitan levels (2-3 times in one month). 2) Parents socialization about agriculture: (a) Almost 74% of respondents felt that their parents never told them about agriculture; (b) Most youth were only involved in the field for planting and harvesting activities, while for other activities, there was still a very lack. 3) However, most young people still see the potential of utilizing land and water resources to meet human needs and still consider agriculture as a good prospect in the future.